Assessing the impact of resource efficiency on selected case studies in Ireland. Issue 4 (14th November 2020) - Göttsche, Jan; Kelly, Mark
Abstract : In the EU, construction and the use of buildings account for 50% of final energy consumption, approximately 35% of greenhouse gas emissions, more than 50% of all extracted materials, 30% of water consumption by the population and 35% of total generated waste, annually. In Ireland, there has been a clear connection between construction output, construction and demolition production and energy use. During this time of economic recovery, there is a unique opportunity to decouple this connection and rethink the built environment to one that embraces material cycles that have net positive environmental benefits. This study used an action research methodology to benchmark the effectiveness of implementing a series of resource efficiency measures during the construction phase of four case studies with a  small-to-medium enterprise building contractor. The implementation of these measures in the case studies produced cost savings of €14 567.70 representing 0.48% of the total project value (€3 050 032). The total energy savings were estimated to be 11 373.09 kWh and it was estimated that 176.751 t of materials were prevented from being placed in site skips. The total reduction in carbon dioxide (CO2 ) emissions from the implemented measures was 52.263 t.